A Small “Tent” in the Esophagus - Zong, Zeng-Min; Xu, Jia-Yun; Zhang, Hai-Tao; Xu, Huan; Tang, Xiao-Wei; Shi, Lei (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Zong Z, Xu J, Zhang H, Xu H, Tang X, Shi L. A small “tent” in the esophagus. Turk J Gastroenterol. 2024;35(7): 587-588.